Science, Utopia and the human condition. (1st January 2013) - Strand, Roger
In science and innovation policies, conceptions of the future enter on multiple levels. This paper is concerned with the implicit conception of the future that appears to be built into the very frame of contemporary science and innovation policies in the knowledge society. Marquis de Condorcet's Sketch for a Historical Picture of the Progress of the Human Mind is discussed as one example of a classic formulation of this conception: The Utopian hope for unlimited increase in wealth and happiness through scientific progress. The paper asks if debates on the plausibility of specific representations of the future, among policy-makers as well as the scholars studying them, rest upon a more fundamental implausible Utopian hope that conceals the vast transformative power of science and technology on the human condition. If this may be the case, the debates should be opened up to broader audiences for re-framing. If plausibility is to be determined, we should ask: whose applause?